2022
DOI: 10.3389/fphar.2022.942996
|View full text |Cite
|
Sign up to set email alerts
|

Dandelion extract inhibits triple-negative breast cancer cell proliferation by interfering with glycerophospholipids and unsaturated fatty acids metabolism

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype with limited treatment options and a poor prognosis. TNBC exists widely reprogrammed lipid metabolism, and its metabolic-associated proteins and oncometabolites are promising as potential therapeutic targets. Dandelion (Taraxacum mongolicum) is a classical herbal medicine used to treat breast diseases based on traditional Chinese medicine theory and was reported to have antitumor effects and lipid regulatory capacities. Our previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Specifically, BC is characterized by substantial metabolic heterogeneity. Therefore, targeting these metabolic alterations represents a promising therapeutic strategy [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, BC is characterized by substantial metabolic heterogeneity. Therefore, targeting these metabolic alterations represents a promising therapeutic strategy [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 60% of TNBC cases exhibit abnormal lipids metabolism pathways. This observation has raised significant interest in exploring metabolic-associated proteins and oncometabolites as promising therapeutic targets [ 54 ]. In a study targeting cancerous cells with dandelion extract, an herbal medicine with antitumor effects and lipid regulatory properties, changes in glycerophospholipids and unsaturated fatty acids emerged as the most prominent metabolite alterations in TNBC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many studies have confirmed the effectiveness of TCM in treating these five types of cancer and have elucidated their mechanisms of action. For instance, Wang et al (2022) reported that dandelion extract inhibited triple-negative breast cancer cell proliferation by interfering with glycerophospholipids and unsaturated fatty acid metabolism. Zhai et al (2022) found that red ginseng polysaccharides exhibited anti-ferroptosis effects in the lung and breast cancer cells by targeting GPX4.…”
Section: Discussionmentioning
confidence: 99%
“…Dandelion is a traditional medicinal and edible plant and has a history of thousands of years in China; it contains not only diverse bioactive components but also high dietary fiber and protein contents, as well as a large variety of amino acids and most minerals and vitamins ( 23 ). Therapeutically, dandelion has broad-spectrum antibacterial, antioxidant, diuretic, anti-inflammatory, and tumor apoptosis-inducing properties and can treat numerous diseases, such as acute inflammatory, neoplastic, urological, and diabetic syndromes ( 24 26 ). Additionally, the dandelion extract is a common antiviral agent used in TCM and has been reported to exhibit antiviral capabilities against HIV-1, influenza virus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and hepatitis B virus ( 27 30 ).…”
Section: Introductionmentioning
confidence: 99%